2002
DOI: 10.1080/01650250143000184
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial influences on possible selves: A comparison of three cohorts of older adults

Abstract: T his study examined the psychosocial factors that in uence the possible selves of older adults in their 60s, 70s, and 80s or older. Speci cally, the factors that in uence when and why health becomes salient in later life were examined. Findings showed that health was the most important domain of self for the oldest group. Although age was the strongest predictor of health-related selves, older males with better health and few physical limitations, were most likely to report health-related selves. Leisure, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…This result accords with several previous findings (e.g. Frazier et al 2002;Lapierre et al 1992Lapierre et al -1993Saajanaho et al 2014a). In old age, health decline becomes a more imminent threat, and goals related to maintaining health and functional status as long as possible become topical.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result accords with several previous findings (e.g. Frazier et al 2002;Lapierre et al 1992Lapierre et al -1993Saajanaho et al 2014a). In old age, health decline becomes a more imminent threat, and goals related to maintaining health and functional status as long as possible become topical.…”
Section: Discussionsupporting
confidence: 94%
“…In old age, health decline becomes a more imminent threat, and goals related to maintaining health and functional status as long as possible become topical. Previously, it has been suggested that health problems in old age may lead to the setting of healthrelated goals (Frazier et al 2002;Lapierre et al 1997). In this study, better health resources increased the likelihood for reporting health maintenance goals and decreased the likelihood for recovery goals.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Since possible selves are conceptualized in a future context, but nevertheless derived from past experiences and expectations, they play an important role in change processes of the self-concept as well as for self-regulation (Cross & Markus, 1991;Dark-Freudeman, West, & Viverito, 2006;Frazier, Johnson, Gonzalez, & Kafka, 2002;Hoyle & Sherrill, 2006;Manzi, Vignoles, & Regalia, 2010). On the one hand, imagining what is possible in the future can function as a motivational incentive for behavior; therefore, possible selves serve as a guide for selection processes (Hoppmann, Gerstorf, Smith, & Klumb.…”
mentioning
confidence: 99%
“…At the level of the individual, research has shown that our sense of self becomes more closely tied to our perceptions of our health as we age (Frazier, Johnson, Gonzalez, & Kafka, 2002;Hooker, 1992;Hooker & Kaus, 1992, 1994. This implies that a positive sense of self is tied to a positive sense of our healthiness or sense of invulnerability, particularly to potentially devastating events such as hip fracture.…”
Section: Feelings Of Invulnerability and Decision-making Styles Amongmentioning
confidence: 93%